PENGARUH KEPEMIMPINAN, FASILITAS KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PERANGKAT DESA ILIRAN KECAMATAN GAUNG ANAK SERKA - DEWITA, NURHEVI; Donal Devi Amdanata (Indragiri Research Center (ingreat), 2023)
The purpose of this research is to determine the influence of leadership, work facilities and work environment on the performance of Sungai Iliran Village officials, Gaung Anak Serka District. The research population is the entire Sungai Iliran Village apparatus, Gaung District, totaling 32 people. The research population uses the census method. The research results show that the leadership variable has a positive direct and significant effect on the performance of village officials, the work facility variable has no positive direct and significant effect on the performance of village officials, the work environment variable has a positive direct and significant effect on the performance of village officials, there is a significant effect from the independent variables of leadership, work facilities, work environment to the dependent variable of Village apparatus performance. Based on the results of the F test, there is a significant influence of the independent variables leadership, work facilities, work environment on the dependent variable performance. The value of the coefficient of determination obtained is 0.958, so it can be concluded that the leadership variables, work facilities, work environment contribute to the performance variable (Y) by 95.8%. Meanwhile, the remaining 4.2% is influenced by other factors outside the independent variables in this study.